Determination of the resistance of water-repellent properties to ultraviolet radiation on self-hydrophobized surface textures of AISI 304 steel - Baklan, Denys (Technology audit and production reserves, 2023)
In this work, the object of the study were femtosecond laser textured steel samples. Using a femtosecond laser to texture the surface both in the direct-beam mode, which provides microtextures, and in the reflection mode, which leads to the formation of LIPSS-type nanostructures on the surface. Such hybrid complexes are optimal in terms of water repellency as they embody the principle of hierarchical textures. This approach is one of the promising ways to solve the problem of scaling the process of obtaining superhydrophobic metal surfaces. The aim of the work is to establish the stability of water-repellent properties of micro- nanotextures obtained on the surface of AISI 304 steel after spontaneous hydrophobization under the action of UV radiation. The study of the obtained textured surface by scanning electron microscopy to confirm the presence of nanotexture and by energy-dispersive X-ray spectroscopy to establish the elemental composition of the obtained microtexture were made in the work. The paper shows that the water repellency of AISI 304 steel surfaces textured at micro and nano levels by femtosecond laser after long exposure to the atmosphere increases to a superhydrophobic state with the value of contact angles up to 155°. It has been shown that such surfaces are sensitive to UV radiation. Depending on the type of structure, the loss of hydrophobicity under experimental conditions occurs in 15-45 minutes of exposure, and complete hydrophilization of the surface occurs after 100 minutes of irradiation. As a result, the obtained self-hydrophobic surfaces are not suitable for operation under the influence of sunlight. However, ultraviolet radiation can be used to pre-clean such surfaces from adsorbed organic contaminants.